2009
DOI: 10.1177/0146167209347322
|View full text |Cite
|
Sign up to set email alerts
|

Emotions as Within or Between People? Cultural Variation in Lay Theories of Emotion Expression and Inference

Abstract: Four studies using open-ended and experimental methods test the hypothesis that in Japanese contexts, emotions are understood as between people, whereas in American contexts, emotions are understood as primarily within people. Study 1 analyzed television interviews of Olympic athletes. When asked about their relationships, Japanese athletes used significantly more emotion words than American athletes. This difference was not significant when questions asked directly about athletes' feelings. In Study 2, when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 22 publications
2
71
1
Order By: Relevance
“…Several studies have found emotions in the United Sates to be understood as arising from the individual, but in Japan as arising from the relationships between individuals [38,39]. These differences in conceptualization are important to both experience and perception.…”
Section: Cultural Construction Of Emotions: Individual-level Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found emotions in the United Sates to be understood as arising from the individual, but in Japan as arising from the relationships between individuals [38,39]. These differences in conceptualization are important to both experience and perception.…”
Section: Cultural Construction Of Emotions: Individual-level Processesmentioning
confidence: 99%
“…Japanese athletes reported more emotions when they described their relationship with others than did American athletes. Japanese respondents also perceived more emotions in athletes who were surrounded by others than did American respondents [38]. Moreover, in several emotion perception studies in which participants judged a target person's emotions [40,41], Japanese used the surrounding people's facial expressions to establish the target person's emotions, but Westerner did not.…”
Section: Cultural Construction Of Emotions: Individual-level Processesmentioning
confidence: 99%
“…It is very well known that many substantial cultural variations have been identified between independent (e.g., Euro-American) and interdependent(e.g., Asian) cultures (Uchida et al, 2004;Uchida et al, 2008;Uchida et al, 2009); however, the present study has obtained the same inner latent factor in countries representing such different cultures. Can the same latent inner factor be extracted from the combined data of US and Japanese respondents?…”
Section: The Same Latent Inner Factor Was Found In Japanese Datamentioning
confidence: 69%
“…In cross-cultural psychology, several authors describe a specific range of emotions, more accessible than others to Japanese (Doi, 1981;Morschbach & Tyler, 1986;Markus & Kitayama, 1991;Kitayama, Mesquita, Karasawa, 2006). Other studies discuss the Japanese cultural scripts, which guide the order of expressing and understanding emotions (Wierzbicka, 1996), emotion inference (Uchida et al, 2009) and co-occurrence of positive and negative emotions in Japan (Miyamoto, Uchida, Ellsworth, 2010;Uchida & Kitayama, 2009). …”
Section: Introductionmentioning
confidence: 99%